Gain-clamped erbium-doped fiber amplifier using a single fiber Bragg grating - Subramaniam, T.; Mahdi, Mohd Adzir; Poopalan, Prabakaran; Harun, Sulaiman Wadi; Ahmad, Harith (John Wiley & Sons, 2001)
A new design of an all-optical gain-clamped erbium-doped fiber amplifier is demonstrated. The amplifier is based on the conventional ring cavity, where the gain is clamped at 21.84 dB via optical feedback using a single fiber Bragg grating for an input signal power as high as -8 dBm.